A novel singular value decomposition-based ultra wide band time-of-arrival estimation for multiple targets - Ibrahim Yassine Nouali; Zohra Slimane; Abdelhafid Abdelmalek (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
It is widely admitted that the estimation of ultra wide band (UWB) time-of-arrival (TOA) for multiple targets in indoor multipath channels is a very challenging task. The existing algorithms deal with a limited number of targets and require a complex exchange of several messages. In this paper, a novel TOA estimation algorithm for multiple targets is developed. The proposed algorithm estimates the first path (FP) TOA of a number of targets without exchanging messages or using collision avoidance techniques. As a first step, the singular value decomposition (SVD) is employed to extract the first path (FP) of each target and then a matched filter, followed by an iterative threshold crossing algorithm, is used to determine the number of targets and the corresponding FP TOAs. The simulation results with four targets, using the CM1 IEEE 802.15.4a channel model, showed that the proposed novel algorithm can effectively detect the FP of each target and estimate its corresponding TOA.